Implementasi Maqashid Syariah dengan Pengembangan Ekonomi Hijau Melalui Urban Farming - Yusvita Nena Arinta (Universitas Islam Negeri (UIN) Walisongo Semarang, Indonesia, 2019)
The trend of conventional economic in emerging countries raises problems in other sectors with systematic. This results in inconsistencies with the main objectives of carrying out economic activities. Economic goals are not only oriented towards wealth, but also protect the living ecosystem (hifdzu-n-nafsi) and also protect offspring (hifdzu-n-nasli). Fundamental corrections are needed to find new ways of economic development. Green economy as a new way to solve economic problems applying Maqashid Shariah. Green economy through Maqashid Shariah focuses on 3 concepts: 1) the quality of economic growth, 2) environmental efficiency, and 3) social growth. As a paradigm that is able to maintain sustainable ecosystems in achieving social economic growth by supporting welfare improvement. Urban farming is becoming a new path of discovery to develop the prosperity of implementing a green economy in Indonesia. Urban farming is an industrial cycle that produces, processes and sells food and energy to meet the needs of city consumers. All activities are carried out by the method of using and reusing natural resources and urban waste. Besides fulfilling the basic needs of every family that is the basis of a measure of money, urban farming is needed to get money with other household needs. The idea of returning to nature shows that urban agriculture is able to meet economic quality growth targets, save energy and social interaction in accordance with Islamic economic principles.